Star-forming, rotating spheroidal galaxies in the GAMA and SAMI Surveys - Moffett, Amanda J; Phillipps, Steven; Robotham, Aaron S G; Driver, Simon P; Bremer, Malcolm N; Cortese, Luca; Wong, O Ivy; Brough, Sarah; Brown, Michael J I; Bryant, Julia J; Conselice, Christopher J; Croom, Scott M; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
The Galaxy And Mass Assembly (GAMA) survey has morphologically identified a class of “Little Blue Spheroid” (LBS) galaxies whose relationship to other classes of galaxies we now examine in detail. Considering a sample of 868 LBSs, we find that such galaxies display similar but not identical colours, specific star formation rates, stellar population ages, mass-to-light ratios, and metallicities to Sd-Irr galaxies. We also find that LBSs typically occupy environments of even lower density than those of Sd-Irr galaxies, where ∼65% of LBS galaxies live in isolation. Using deep, high-resolution imaging from VST KiDS and the new Bayesian, two-dimensional galaxy profile modeling code PROFIT, we further examine the detailed structure of LBSs and find that their Sérsic indices, sizes, and axial ratios are compatible with those of low-mass elliptical galaxies. We then examine SAMI Galaxy survey integral field emission line kinematics for a subset of 62 LBSs and find that the majority (42) of these galaxies display ordered rotation with the remainder displaying disturbed/non-ordered dynamics. Finally, we consider potential evolutionary scenarios for a population with this unusual combination of properties, concluding that LBSs are likely formed by a mixture of merger and accretion processes still recently active in low-redshift dwarf populations. We also infer that if LBS-like galaxies were subjected to quenching in a rich environment, they would plausibly resemble cluster dwarf ellipticals. Peer reviewed